PENGARUH PERSEPSI PENGGUNA TERHADAP KEMANFAATAN DAN SELF-IMAGE CONGRUITYTERHADAP KEBIASAAN, KEPERCAYAAN DAN NIAT BELI BERKELANJUTAN (STUDI SURVEI PADA KONSUMEN MATAHARIMALL.COM) - Siagian, Harry Yunizar (Jurnal Manajemen USNI, 2017)
The purpose of this study was to analyze the effect on percieved usefulness, and self image congruity on habit, trust, andcontinuance intention(consumer survey study onmataharimall.com). Continuance intention is assumed to be significantly affected by percieved usefulness, self image congruity, habit and trust. Explanatory research reported here aimed to test the hypothesis. This is done through a survey of consumers who have been using the service mataharimall.com. Samples of 160 people chosen at random. Data from each of the variables were collected through questionnaires. The analysis technique using Structural Equation Modeling (SEM) with a measurement model Confirmatory Factor Analysis (CFA). The findings indicate that percieved usefulness significant effect on the habits, trust and continuance intention. Self-image congruity proved no effect on confidence but sustained effect on continuance intention. Habits proved significantly influence continuance intention. Trust proved no effect on continuance intention mataharimall.com.